2008
DOI: 10.1073/pnas.0800367105
|View full text |Cite
|
Sign up to set email alerts
|

Fecal transmission of AA amyloidosis in the cheetah contributes to high incidence of disease

Abstract: AA amyloidosis is one of the principal causes of morbidity and mortality in captive cheetahs (Acinonyx jubatus), which are in danger of extinction, but little is known about the underlying mechanisms. Given the transmissible characteristics of AA amyloidosis, transmission between captive cheetahs may be a possible mechanism involved in the high incidence of AA amyloidosis. In this study of animals with AA amyloidosis, we found that cheetah feces contained AA amyloid fibrils that were different from those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 41 publications
1
107
0
3
Order By: Relevance
“…While AA amyloid fibrils were not detected in cheetah urine, cheetah feces unexpectedly contained AA amyloid fibrils that differed from those seen in the liver. Compared with liver amyloid fibrils, fecal amyloid fibrils had a smaller molecular weight due to deletion of both N-and C-terminal sequences, a shorter and finer fibrillar shape on electron microscopy, 82 and increased sensitivity to denaturation treatments, such as incubation in 6 M guanidine hydrochloride solution. Interestingly, comparison of the transmissibility of fecal and liver AA amyloid fibrils using the mouse experimental AA amyloidosis system showed that the fecal amyloid fibrils from the cheetah exhibited significantly greater transmissibility.…”
Section: 35mentioning
confidence: 99%
See 1 more Smart Citation
“…While AA amyloid fibrils were not detected in cheetah urine, cheetah feces unexpectedly contained AA amyloid fibrils that differed from those seen in the liver. Compared with liver amyloid fibrils, fecal amyloid fibrils had a smaller molecular weight due to deletion of both N-and C-terminal sequences, a shorter and finer fibrillar shape on electron microscopy, 82 and increased sensitivity to denaturation treatments, such as incubation in 6 M guanidine hydrochloride solution. Interestingly, comparison of the transmissibility of fecal and liver AA amyloid fibrils using the mouse experimental AA amyloidosis system showed that the fecal amyloid fibrils from the cheetah exhibited significantly greater transmissibility.…”
Section: 35mentioning
confidence: 99%
“…52 We examined the possibility of horizontal transfer or transmission of AA amyloidosis in a group of captive cheetah with severe AA amyloid deposition in the kidney, liver, and spleen, as well as in other organs. 82 The AA fibril protein isolated from the liver was equivalent to the N-terminal part of the precursor protein SAA (the longest AA peptides consisted of amino acids 1-93 of the 111-amino acid, full-length precursor protein). While AA amyloid fibrils were not detected in cheetah urine, cheetah feces unexpectedly contained AA amyloid fibrils that differed from those seen in the liver.…”
Section: 35mentioning
confidence: 99%
“…43 Laboratory experiments demonstrated the host-to-host transmission of AA amyloidosis. 44 However, no epidemiological data support the natural host-tohost transmission of any of these diseases other than TSEs.…”
Section: Prion-like Mechanisms and Prionoid Proteinsmentioning
confidence: 99%
“…We hypothesize that the propagation of AA amyloidosis among captive cheetah populations may depend on a horizontal transmission pathway (B. Zhang et al, 2008). Captive cheetahs with severe AA amyloidosis were studied.…”
Section: Transmission Of Aa Amyloidosis In Cheetah and Cattlementioning
confidence: 99%